Ciało, moda i tozsamosc kobiety epoki wiktorianskiej – dyskursy piekna i przemocy - Gromkowska-Melosik, Agnieszka (Kultura-Społeczeństwo-Edukacja, 2012)
The article is devoted to the analysis of the dominant ideal of beauty in the Victorian period. The author defi nes mechanisms of repression and symbolic violence over the body of the Victorian upper-class woman, connected with the phenomenon of social control over the woman’s body and identity. The author assumes that the desire to achieve physical beauty has always been a source of a biographical experience that was constitutive for a woman, a source of a separate identity for her in comparison with a man. The historical changes of the ideals of the beautiful body are expressive of the complex interactions between the social roles of women and the dominant ideology of femininity as well as scientifi c and medical knowledge.